Coding for Medication-related Poisoning and Adverse Effects. Issue 3 (June 2017) - Yu, Melissa
Abstract : ABSTRACT: Accurate coding is important for proper reimbursement and documentation of care provided. This article provides an overview of coding considerations for patient encounters associated with medication use, abuse, or poisoning.